2018
DOI: 10.1038/s41598-018-29501-8
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the blocking model to fit nanoparticle ZFC/FC magnetisation curves

Abstract: We consider the probability of a magnetic nanoparticle to flip its magnetisation near the blocking temperature, and use this to develop quasi-analytic expressions for the zero-field-cooled and field-cooled magnetisation, which go beyond the usual critical energy barrier approach to the superparamagnetic transition. The particles in the assembly are assumed to have random alignment of easy axes, and to not interact. We consider all particles to be of the same size and then extend the theory to treat polydispers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 30 publications
(45 reference statements)
6
66
0
Order By: Relevance
“…Interestingly, the peak width is not negligible and varies, while no size dispersion is considered. So it comes from the stochastic nature of thermally induced spin reversal in a finite temperature range, consistent with the conclusion drawn by Livesey et al when calculating T B SP in monodisperse samples . As a result, a large K SG deepens energy barriers and traps spins at higher temperatures, meanwhile the high temperature enhances uncertainty of spin reversal, resulting in a short and wide peak.…”
supporting
confidence: 84%
See 2 more Smart Citations
“…Interestingly, the peak width is not negligible and varies, while no size dispersion is considered. So it comes from the stochastic nature of thermally induced spin reversal in a finite temperature range, consistent with the conclusion drawn by Livesey et al when calculating T B SP in monodisperse samples . As a result, a large K SG deepens energy barriers and traps spins at higher temperatures, meanwhile the high temperature enhances uncertainty of spin reversal, resulting in a short and wide peak.…”
supporting
confidence: 84%
“…In noninteracting nanoparticles, T irr is obtained through measurements of magnetization made in the zero‐field‐cooled (ZFC) and field‐cooled (FC) regimes as a function of temperature . In this kind of experiment, a sample is cooled from a temperature where all particles show super paramagnetic behavior to a target low temperature, then a constant field is applied and the sample is heated to a temperature high enough to observe an initial growth and subsequent decrease of its magnetization.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our model can also be used to study the blocking temperature in relation to the field-cooled and zero-field cooled magnetization, extending previous studies on non-interacting MNPs. 34 Some authors found it necessary to include distributions of magnetic anisotropy constants, representing the energy barriers of individual particles. 12 This could be incorporated in the present model by a distribution of L 0 values.…”
Section: Model Formulationmentioning
confidence: 99%
“…Let n denote the orientation of the ordering field. We assume that the magnetization remains parallel to n during the relaxation where the field has been switched off, hui = U B n. Assuming furthermore uniaxial symmetry, huui = S 2 nn + (1 À S 2 )I/3, where I denotes the threedimensional unit matrix, we can rewrite eqn (34) as…”
mentioning
confidence: 99%